Effect of Fe(III) on the positive electrolyte for vanadium redox flow battery. Issue 1 (23rd January 2019) - Ding, Muqing; Liu, Tao; Zhang, Yimin; Cai, Zhenlei; Yang, Yadong; Yuan, Yizhong
Abstract : It is important to study the effect of Fe(III) on the positive electrolyte, in order to provide some practical guidance for the preparation and use of vanadium electrolyte. The effect of Fe(III) on the thermal stability and electrochemical behaviour of the positive electrolyte for the vanadium redox flow battery (VRFB) was investigated. When the Fe(III) concentration was above 0.0196 mol l −1, the thermal stability of V(V) electrolyte was impaired, the diffusion coefficient of V(IV) species decreased from (2.06–3.33) × 10 −6 cm 2 s −1 to (1.78–2.88) × 10 −6 cm 2 s −1, and the positive electrolyte exhibited a higher electrolyte resistance and a charge transfer resistance. Furthermore, Fe(III) could result in the side reaction and capacity fading, which would have a detrimental effect on battery application. With the increase of Fe(III), the collision probability of vanadium ions with Fe(III) and the competition with the redox reaction was aggravated, which would interfere with the electrode reaction, the diffusion of vanadium ions and the performance of VRFB. Therefore, this study provides some practical guidance that it is best to bring the impurity of Fe(III) below 0.0196 mol l −1 during the preparation and use of vanadium electrolyte.